Writing the history of crime - Knepper, Paul (Writing history, 2016)
Legal history -- Statistics, trends and techniques -- Evolution and psychoanalysis -- The British Marxist historians -- The city and its' criminals -- Foucault's project -- Women, gender and crime -- Colonial and international